DIGITAL DEVICES, PLAY AND EMERGENT LITERACY IN EARLY CHILDHOOD - Nia Roistika; M.Choirul Huda (STKIP PGRI TULUNGAGUNG, 2025)
In this paper, we examined articles between 2000 and 2024. This time span was selected as the mark of growing digital devices around 2000’s. This paper aims at collecting and gathering the journal articles. The col-lecting and gathering stages were started by academic database by em-ploying three search Strings. The process of collecting and gathering journal articles were focused on the roles of play during early childhood, the second point deliberating how technology tools support children in play process, followed by the digital devices promoted emergent litera-cy, the benefit and disadvantage of the technology advancement to children’s life and development, finally this paper ends up by giving concluding remark and the future recommendation.